Contemporary agrarian question and alternative ways to its solution1 - Czyżewski Andrzej; Staniszewski Jakub (Management)
Article presents a complex problem of an agrarian question - its causes, consequences and ways of mitigating the negative effects associated with it. Featured, competing models of agricultural development - industrial and sustainable, are characterized. Also the negative effects of excessive industrialization of agricultural production, leading to the failure of this model, are shown. At the same time, as an alternative, authors indicate sustainable agricultural model, engaging in its account economic, social and environmental costs. As an example of the transition from the industrial model to sustainable development model, the EU common agricultural policy has been described, including its future form in the financial perspective 2014-2020.